2022
DOI: 10.3390/ma15103636
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Titanium Particles Released from Bone-Level Titanium Dental Implants: Effect of the Size of Particles on the Ion Release and Cytotoxicity Behaviour

Abstract: Many studies are being carried out on the particles released during the implantoplasty process in the machining of dental implants to remove bacterial biofilms. However, there are no studies on the release of particles produced by the insertion of bone-level dental implants due to the high compressive frictional loads between the rough titanium implant and the bone tissue. This paper aims to characterize the released particles and determine the release of titanium ions into the physiological environment and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
6
0
3
Order By: Relevance
“…For cp-Ti alloys, the presence of a self-passive titanium dioxide (TiO 2 ) layer ensured high corrosion resistance in different simulated body fluid environments [ 12 , 13 ]. Due to the presented properties of commercially pure titanium, their applications include dental implants [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For cp-Ti alloys, the presence of a self-passive titanium dioxide (TiO 2 ) layer ensured high corrosion resistance in different simulated body fluid environments [ 12 , 13 ]. Due to the presented properties of commercially pure titanium, their applications include dental implants [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, particles of different sizes were isolated by simulating implantoplasty processes with more than 200 titanium dental implants, and they were classified into different mean sizes of 5 µm (Ti-5), 10 µm (Ti-10), 15 µm (Ti-15), and 30 µm (Ti-30). The reason for choosing these particle sizes is due to the fact that, in the literature, they are the most common ones found in the tissues after implantoplasty processes [20][21][22][23][24][25] and after the placement of bone-level dental implants caused by the friction of the collar on the cortical bone [26][27][28]. A limitation of this type of study is the difficulty in determining and characterizing particles smaller than 1 µm in size, although they can be observed in small quantities through field-emission electron microscopy observations and micro-CT characterization.…”
Section: Introductionmentioning
confidence: 99%
“…However, as they are inserted into the oral cavity, they can be subjected to corrosion and wear phenomena, with consequent release of metal ions into the human body [ 4 , 5 , 6 ]. These released metal ions and particles may have deleterious systemic and local effects; for instance, they are related to the failure of implant-supported oral rehabilitations and thus matter of concern for the scientific community [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This standpoint is corroborated by Kunrath et al [ 12 ], who considered the long-term behavior of fragments of certain chemical elements in tissues or cells at the molecular level and indicated that this is still not well-understood. Ion release from metallic prosthetic devices is a current issue and the object of many recent studies [ 11 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%